Analisis Efisiensi Daya pada Otomatisasi Sistem Kendali Kecepatan Fan Cooling Tower Unit PLTP #2 - Erna Kusuma Wati (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Analysis the efficiency for the use of motors that place in Geothermal Powerplant #2, by implementing automated system for the control of 's speed mode so that the financial and non-financial benefits can be obtained. Automation system in controlling the cooling tower fan speed mode in order to adjust conditions in the safe category, so that power efficiency can be applied continuously by minimizing decision errors or negligence in operation. The analysis based on the operation characteristics, the design of the generation plant, heat balance modeling simulation, and the related laws of physics and mathematical equations. By considering the reliability of the generation powerplant. Obtained a change in the operating pattern of the cooling tower fan from initially operating entirely in high speed mode (5H0L) to 4 fans in high speed mode and 1 fan in low speed mode (4H1L), with the power efficiency obtained from the success of the change amounting to 58.72 kW.